Improving the Students’ Speaking Ability of Report Text through Stop Motion Video Technique in Junior High School - Fikry Aji Wicaksono; Isma Hidayati; Widya Eka Septiani (STKIP PGRI SIDOARJO, 2021)
This research was Classroom Action Research. This research aimed at implementing stop motion video technique to improve students speaking ability of report text in junior high school and the students’ perception in implementation of stop motion video technique to improve the students’ speaking ability of report text. The subject of this research was the second grade of junior high school. The focus of this research was the students’ speking ability. The data were in the form of students’ speaking score. The data were obtained through conducting teaching learning process. The result of this research was that there were improvement in students’ speaking ability through Stop Motion Video technique in whole skills. The improvement was up to 40%-90%. They were pronunciation, grammar, vocabulary, fluency, and understanding. The students’ perception showed that all of the students were motivated after conducted this learning technique. This was showed by the questionnaires filled by the students.